Efficacy of Telitacicept in treating IgA vasculitis nephritis: a two-case report - Li, Shuang-xi; Hu, Rui-kang; Kong, De-liang; Xu, Jing; Bian, Qi; Guo, Zhi-Yong; Mei, Xiao-bin (Frontiers in Immunology, 2025)
Telitacicept, a B lymphocyte stimulator/A proliferation-inducing ligand dual-target fusion protein, mainly used for IgA nephropathy and systemic lupus erythematosus. We present two cases where adult patients with IgA vasculitis (IgAV) nephritis were successfully treated with Telitacicept, experienced no adverse reactions during the follow-up. Therefore, Telitacicept represents a promising additional treatment option for patients suffering from IgA vasculitis (IgAV).